Zirconia sintered body and production method thereof
A zirconia sintered body with controlled yttria content and crystal grain distribution addresses the challenge of achieving both translucency and strength in dental prosthetics, enabling manufacturing in standard atmospheric pressure furnaces.
Patent Information
- Application Number
- JP2024188642
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-10-08
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-20
AI Technical Summary
Zirconia sintered bodies used in dental prosthetics face challenges in achieving both high translucency and mechanical strength, particularly when a high content of stabilizers is required, leading to difficulties in manufacturing using conventional sintering furnaces that operate under atmospheric pressure.
A zirconia sintered body with a yttria content of 4.5 mol% to 6.5 mol% and specific crystal grain size and distribution, along with controlled sintering conditions, is developed to maintain translucency while enhancing mechanical strength, suitable for dental prosthetic materials.
The solution provides a zirconia sintered body with improved mechanical strength and translucency, suitable for dental prosthetics, manufactured using standard atmospheric pressure sintering furnaces.
Smart Images

Figure 2025010231000005 
Figure 2025010231000006 
Figure 2025010231000001
Abstract
Description
[Technical field]
[0001] Zirconia sintered bodies used in dental prosthetic materials such as crowns and bridges are required to have translucency equivalent to that of natural teeth. In order to meet this requirement, studies have been conducted to improve the translucency of zirconia sintered bodies by increasing the content of a stabilizer (Patent Document 1). While increasing the content of a stabilizer improves the translucency of the zirconia sintered body, it also reduces its mechanical strength. For this reason, it has been difficult to apply the zirconia sintered bodies of Patent Document 1 and the like as dental prosthetic materials, which require particularly high mechanical strength.
[0002] Patent Document 2 considers improving the mechanical strength of a zirconia sintered body with a high stabilizer content, and discloses a zirconia sintered body that can satisfy the mechanical strength required for dental prosthetic materials, which require particularly high mechanical strength, despite the stabilizer content that may cause a decrease in mechanical strength. Similarly, Patent Document 3 discloses a zirconia sintered body that can satisfy the mechanical strength required for most dental prosthetic materials by controlling the sintering atmosphere, even in the range of a stabilizer content of 5 mol% or more, where the mechanical strength is significantly decreased. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-143178 A [Patent Document 2] JP 2018-052806 A [Patent Document 3] JP 2011-073907 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the manufacture of dental prosthetic materials, a sintering furnace that performs sintering in an air atmosphere and under atmospheric pressure is widely used. Therefore, it is difficult to use a zirconia sintered body manufactured by sintering that requires dedicated equipment such as hot isostatic pressing (HIP) or microwave sintering, or by sintering that requires atmospheric control such as an oxygen atmosphere, as a zirconia sintered body for use in a dental prosthetic material.
[0005] An object of the present disclosure is to provide at least one of a zirconia sintered body that can be produced even using a sintering furnace that performs sintering under atmospheric pressure and that has the mechanical strength and translucency required for a dental prosthetic material, a manufacturing method thereof, a precursor thereof, and a manufacturing method of the precursor. [Means for solving the problem]
[0006] In the present disclosure, in light of the fact that sintering in an air atmosphere under atmospheric pressure is widely used in the manufacture of dental prostheses, the authors have investigated the compatibility of mechanical strength and translucency of a zirconia sintered body with a high yttria content. As a result, they have found a zirconia sintered body with a high stabilizer content that is not too transparent and has improved mechanical strength while retaining translucency suitable for dental prostheses.
[0007] That is, the present invention relates to the invention described in the claims, and the gist of the present disclosure is as follows. [1] A zirconia sintered body comprising yttria and zirconia, the yttria content being 4.5 mol% or more and 6.5 mol% or less, the remainder being zirconia, the total light transmittance measured in accordance with JIS K 7361-1 for a sample thickness of 1 mm being 46.5% or more, the three-point bending strength being 700 MPa or more, and the ratio of the integrated value of the linear transmittance to the integrated value of the total light transmittance being 1.3% or less, at a sample thickness of 1 mm and a measurement wavelength of 400 to 700 nm. [2] The zirconia sintered body according to the above [1], which contains alumina. [3] The zirconia sintered body according to [1] or [2] above, having an alumina content of 0.005% by mass or more and 0.2% by mass or less. [4] The zirconia sintered body according to any one of [1] to [3] above, having an average crystal grain size of 0.5 μm or more and 1.8 μm or less. [5] The zirconia sintered body according to any one of [1] to [4] above, comprising crystal grains having different yttria concentrations. [6] The zirconia sintered body according to any one of [1] to [5] above, wherein the difference in yttria concentration between the crystal grains having the maximum yttria concentration and the crystal grains having the minimum yttria concentration is 2.7 mol% or more and 7 mol% or less. [7] The zirconia sintered body according to any one of [1] to [6] above, wherein the number ratio of crystal grains having an yttria concentration of 3.0 mol% or more and 4.0 mol% or less among the crystal grains is 10% or more and 50% or less. [8] A method for producing a zirconia-based zirconia-based zirconia powder comprising the steps of: (a) supplying zirconia to a sintered body; (b) supplying zirconia to a sintered body; and (c) supplying zirconia to a sintered body; 2 / g or more 15m 2 10. The method for producing a zirconia sintered body according to any one of the above [1] to [7], further comprising a step of sintering a green body containing zirconia powder having a molecular weight of 1000 to 10000 kJ / g or less and an average crystallite size of 325 Å or more. [9] The method according to [8] above, wherein the zirconia powder comprises zirconia powder particles having different yttria contents.
[10] The method according to the above [9], wherein the difference in yttria content between one zirconia powder particle and the other zirconia powder particle in the zirconia powder exceeds 3.0 mol %.
[11] The method according to any one of the above [9] to
[10] , wherein the sintering in the step is pressureless sintering.
[12] A method for producing a zirconia-based composite material comprising the steps of: (a) providing an yttria source and zirconia; (b) providing a zirconia-based composite material having a yttria source content of 4.5 mol% or more and 6.5 mol% or less; and (c) providing a zirconia-based composite material having a BET specific surface area of 7.5 m2 or less; 2 / g or more 15m 2 / g or less and an average crystallite diameter of 325 Å or more.
[13] A method for producing a calcined body, comprising using the zirconia powder described in
[12] above. Effect of the Invention
[0008] The present disclosure makes it possible to provide at least one of a zirconia sintered body that can be produced even using a sintering furnace that performs sintering under atmospheric pressure and that has the mechanical strength and translucency required for a dental prosthetic material, a manufacturing method thereof, a precursor thereof, and a manufacturing method of the precursor. [Brief description of the drawings]
[0009] [Figure 1] SEM observation diagram of the surface of the zirconia sintered body of Example 1 [Diagram 2] A graph showing the relationship between the number of crystal grains with an yttria concentration of 3 to 4 mol% in a zirconia sintered body and the three-point bending strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the zirconia sintered body of the present disclosure will be described with reference to an example of an embodiment.
[0011] The zirconia sintered body of the present embodiment contains yttria and zirconia, has an yttria content of 4.5 mol% or more and 6.5 mol% or less, with the remainder being zirconia, has a total light transmittance of 46.5% or more measured in accordance with JIS K 7361-1 for a sample thickness of 1 mm, a three-point bending strength of 700 MPa or more, and has a ratio of the integrated value of the linear transmittance to the integrated value of the total light transmittance at a sample thickness of 1 mm and a measurement wavelength of 400 to 700 nm of 1.3% or less.
[0012] In this embodiment, the "zirconia sintered body" is a sintered body having zirconia as a main phase, and is a sintered body having the highest ratio of zirconia (ZrO2) in the total composition of the sintered body. The mass ratio of zirconia (ZrO2) to the mass of the zirconia sintered body (when zirconia contains a stabilizer, the total mass ratio of the stabilizer and zirconia) is 95% by mass or more and 100% by mass or less, further 99% by mass or less, and further 99.5% by mass or more and 100% by mass or less.
[0013] The zirconia sintered body of this embodiment contains yttria and zirconia. Yttria (Y2O3) functions as a stabilizer without coloring zirconia. Therefore, the zirconia sintered body of this embodiment can be considered as an yttria-containing zirconia sintered body, an yttria-dissolved zirconia sintered body, an yttria-stabilized zirconia sintered body, an yttria-partially stabilized zirconia sintered body, or a partially stabilized zirconia sintered body. The zirconia sintered body of this embodiment preferably contains yttria and zirconia as yttria-containing zirconia. Moreover, it is more preferable that at least a part of yttria is dissolved in zirconia, and that zirconia does not contain undissolved yttria.
[0014] In this embodiment, "not containing undissolved yttria" means that in the XRD measurement and XRD pattern analysis described below, no XRD peak derived from yttria (Y2O3) is confirmed, and it is permissible for the zirconia sintered body of this embodiment to contain undissolved yttria to an extent that does not affect the properties of the zirconia sintered body of this embodiment.
[0015] The yttria content is 4.5 mol% or more and 6.5 mol% or less, and is preferably more than 4.5 mol% and 6.0 mol% or less, 4.7 mol% or more and 5.8 mol% or less, 4.8 mol% or more and 5.5 mol% or less, or 5.0 mol% or more and 5.5 mol% or less. In another embodiment, the yttria content is 4.5 mol% or more, more than 4.5 mol%, 4.7 mol% or more, 4.8 mol% or more, or 5.0 mol% or more, and is 6.5 mol% or less, 6.0 mol% or less, 5.8 mol% or less, or 5.5 mol% or less. If the yttria content is less than 4.5 mol%, it is difficult to stably obtain a zirconia sintered body having high translucency. On the other hand, if the yttria content exceeds 6.5 mol%, the mechanical strength decreases. Since a zirconia sintered body having high translucency can be easily obtained with good reproducibility even in repeated production, the yttria content is preferably 5.0 mol% or more and 6.0 mol% or less, 5.0 mol% or more and 5.8 mol% or less, or 5.2 mol% or more and 5.6 mol% or less.
[0016] The yttria content in the zirconia sintered body of this embodiment is the molar ratio (mol%) of yttria (Y2O3) to the total of zirconia (ZrO2) and yttria (Y2O3) in the zirconia sintered body, and is calculated from {Y2O3 [mol] / (ZrO2+Y2O3) [mol]}×100.
[0017] The zirconia sintered body of this embodiment may contain alumina (Al2O3) or may be composed of zirconia, yttria and alumina. The alumina content may be, for example, 0% by mass or more and 0.2% by mass or less, 0% by mass or more and 0.15% by mass or less, or 0% by mass or more and less than 0.1% by mass. Since the inclusion of a small amount of alumina facilitates sintering, the alumina content may be, for example, more than 0% by mass and 0.2% by mass or less, 0.005% by mass or more and 0.15% by mass or less, 0.01% by mass or more and 0.12% by mass or less, 0.015% by mass or more and less than 0.1% by mass, or 0.02% by mass or more and 0.07% by mass or less.
[0018] The alumina content in the zirconia sintered body of the present embodiment is the mass ratio (mass%) of alumina to the total of zirconia (ZrO2), yttria (Y2O3), and alumina (Al2O3) in the zirconia sintered body, and is calculated from {Al2O3 [g] / (ZrO2+Y2O3+Al2O3) [g]}×100.
[0019] As long as the effect of the zirconia sintered body of this embodiment is not impaired, an element having a function of coloring zirconia (hereinafter, also referred to as a "colorant") may be contained. The colorant may be an element having a function of coloring zirconia and having a function of suppressing the phase transition of zirconia. Specific examples of the colorant include at least one of transition metal elements and lanthanoid rare earth elements, preferably one or more selected from the group consisting of iron (Fe), cobalt (Co), nickel (Ni), manganese (Mn), praseodymium (Pr), neodymium (Nd), europium (Eu), gadolinium (Gd), terbium (Tb), erbium (Er) and ytterbium (Yb), more preferably one or more selected from the group consisting of iron, cobalt, manganese, praseodymium, neodymium, terbium and erbium, and even more preferably one or more selected from the group consisting of iron, cobalt and erbium.
[0020] The zirconia sintered body of this embodiment may contain inevitable impurities such as hafnia (HfO2). The content of hafnia as an inevitable impurity is 2.0 mass% or less. However, it is preferable that the zirconia sintered body of this embodiment does not contain elements that have a large effect on the effect of the zirconia sintered body of this embodiment. For example, the zirconia sintered body of this embodiment satisfies at least one of the following: the content of magnesium calculated as magnesia (MgO) is 0 mass ppm or more and 500 mass ppm or less, the content of silicon calculated as silica (SiO2) is 0 mass ppm or more and 500 mass ppm or less, and the content of titanium calculated as titania (TiO2) is 0 mass ppm or more and 500 mass ppm or less. It is preferable that the contents of magnesium, silicon, and titanium are each 0 mass ppm or more and 500 mass ppm or less.
[0021] The composition of the zirconia sintered body of this embodiment can be measured by a general composition analysis (for example, ICP measurement). In another embodiment, if the manufacturing method is known, it can be determined from the composition of the raw materials used.
[0022] The zirconia sintered body of this embodiment preferably contains at least one of tetragonal and cubic crystals in the crystal phase, and more preferably contains tetragonal and cubic crystals. The zirconia sintered body of this embodiment preferably contains at least one of tetragonal and cubic crystals as the main phase in the crystal phase, and the total ratio of tetragonal and cubic crystals in the crystal phase (hereinafter also referred to as "tetragonal + cubic crystal ratio") is preferably 95% or more, or 99% or more. In this embodiment, the crystal phase other than tetragonal and cubic crystals in the crystal phase may be regarded as monoclinic. The ratio of monoclinic crystals in the crystal phase (hereinafter also referred to as "monoclinic crystal ratio") is 0% or more or 0.5% or more, and is less than 5%, preferably less than 1%.
[0023] The tetragonal + cubic crystal ratio and the monoclinic crystal ratio are values calculated from the powder X-ray diffraction (hereinafter also referred to as "XRD") pattern of the surface of the zirconia sintered body of this embodiment by the following formula.
[0024] f T+C =[I t (111)+I c (111)] / [I m (111)+I m (11-1)+I t (111)+I c (111)] f M =1-f T+C In the above formula, f T+C is the tetragonal + cubic crystal ratio, f M is the monoclinic fraction, I t (111) is the surface intensity of the tetragonal (111) plane, I c (111) is the surface intensity of the cubic (111) plane, I m (111) is the surface intensity of the monoclinic (111) plane, and I m(11-1) is the area intensity of the monoclinic (11-1) plane.
[0025] The area intensity of each crystal plane can be obtained by profile fitting the XRD pattern after smoothing and background removal processing using a divided pseudo-Voigt function. Smoothing processing, background processing, and analysis of the XRD pattern such as calculation of area intensity can be performed using an analysis program attached to the X-ray diffraction device (for example, integrated powder X-ray analysis software PDXL Ver.2.2, manufactured by RIGAKU Corporation).
[0026] The XRD pattern of the surface of the zirconia sintered body of this embodiment is preferably obtained by XRD measurement under the following conditions.
[0027] Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ=26°~33° The XRD measurement can be carried out using a general X-ray diffraction device (for example, MiniFlex, manufactured by RIGAKU Corporation).
[0028] Examples of XRD peaks corresponding to each crystal plane of zirconia measured in the above-mentioned XRD measurement include XRD peaks having peak tops at the following 2θ.
[0029] XRD peak corresponding to monoclinic (111) plane: 2θ=31±0.5° XRD peak corresponding to monoclinic (11-1) plane: 2θ=28±0.5° XRD peak corresponding to tetragonal (111) plane: 2θ=30±0.5° XRD peak corresponding to cubic (111) plane: 2θ=30±0.5° The XRD peak corresponding to the tetragonal (111) plane and the XRD peak corresponding to the cubic (111) plane are measured as a single overlapping peak. Therefore, I t (111)+I c (111) can be determined from the integrated intensity of one XRD peak having a peak top at 2θ=30±0.5°.
[0030] The zirconia sintered body of the present embodiment preferably has a relative density of 99.8% or more, or 99.85% or more. The relative density is 100% or less, and further preferably 99.98% or less.
[0031] In this embodiment, the "relative density" is the ratio (%) of the measured density to the theoretical density. The measured density is the ratio (g / cm) of the volume measured by the Archimedes method to the mass measured by mass measurement. 3 The theoretical density, that is, the theoretical density used in this embodiment, is the density (g / cm 3 ) calculated from the following formulas (1) to (4). 3 ).
[0032] A = 0.5080 + 0.06980X / (100 + X) (1) C=0.5195-0.06180X / (100+X) (2) ρ Z =[124.25(100-X)+225.81X] / [150.5(100+X)A 2 C] (3) ρ0=100 / [(Y / 3.987)+(100-Y) / ρ Z ] (4) In equations (1) to (4), ρ0 is the theoretical density, ρ Z is the theoretical density of zirconia, A and C are constants, X is the molar ratio (mol%) of yttria to the total of zirconia (ZrO2) and yttria (Y2O3), and Y is the mass ratio (mass%) of alumina to the total of zirconia, yttria, and alumina in the zirconia sintered body.
[0033] In addition, when the zirconia sintered body of the present embodiment contains a metal oxide or a rare earth oxide other than zirconia, yttria, and alumina, the terms "Y" and "(Y / 3.987)" in the above formula (4) may be replaced as follows.
[0034] Y = Y1 + Y2 + Y n (Y / 3.987)=(Y1 / W1+Y2 / W2+...Y n / W n ) Here, Y1, Y2, , Y n is the mass percentage (mass%) of each metal oxide other than zirconia and yttria, and W1, W2, . . . , W n is the density (g / cm3) of each metal oxide or rare earth oxide other than zirconia and yttria. 3 ) In addition, since the formulas (1) to (4) are values taking into consideration inevitable impurities, it is not necessary to substitute the formula (4) for hafnia, which is an inevitable impurity.
[0035] The zirconia sintered body of this embodiment may have an average crystal grain size of 0.5 μm or more and 1.8 μm or less, or 0.55 μm or more and 1.6 μm or less. The smaller the average crystal grain size of the zirconia sintered body, the higher the mechanical strength tends to be, but the zirconia sintered body of this embodiment is likely to have high mechanical strength even if the average crystal grain size is 0.5 μm or more within the range of the yttria content. The average crystal grain size is preferably 0.5 μm or more and 1 μm or less, 0.55 μm or more and 0.8 μm or less, 0.6 μm or more and less than 0.8 μm, or 0.7 μm or more and less than 0.8 μm.
[0036] The "average crystal grain size" in this embodiment can be determined by a planimetric method using an SEM observation image. That is, a circle with a known area is drawn on the SEM observation image, and the number of crystal grains within the circle (Nc) and the number of crystal grains on the circumference of the circle (Ni) are measured so that the total number of crystal grains (Nc+Ni) is 250±50. Then, the average crystal grain size can be determined using the following formula.
[0037] Average grain size=2 / {π×(Nc+(1 / 2)×Ni) / (A / M 2 )} 0.5 In the above formula, Nc is the number of crystal grains in a circle, Ni is the number of crystal grains on the circumference of the circle, A is the area of the circle, and M is the magnification of the scanning electron microscope observation (for example, 5,000 to 10,000 times). If the number of crystal grains (Nc + Ni) in one SEM observation image is less than 200, (Nc + Ni) can be set to 250 ± 50 using multiple SEM observation images.
[0038] The zirconia sintered body to be subjected to SEM observation may be a zirconia sintered body having a surface roughness of Ra≦0.02 μm that has been subjected to thermal etching (for example, in air at 1400° C. to 1500° C.).
[0039] The zirconia sintered body of the present embodiment may contain crystal grains of different sizes, preferably contains coarse crystal grains and fine crystal grains, and more preferably has a structure in which a coarse crystal grain and a plurality of fine crystal grains form a grain boundary. Specifically, as shown by the circle in Fig. 1, it can be exemplified as having a structure in which crystal grains are distributed so that the periphery of a crystal grain with a major axis (the longest length of the crystal grain) of 1.0 μm or more is surrounded by crystal grains with a major axis of less than 1.0 μm.
[0040] The zirconia sintered body of the present embodiment preferably contains crystal grains having different yttria concentrations, and more preferably is composed of crystal grains having different yttria concentrations. In general, zirconia sintered bodies are composed of crystal grains having the same yttria concentration. In contrast, when a zirconia sintered body is composed of crystal grains having different yttria concentrations, it tends to have properties in which the properties of each crystal grain are synergistically reflected.
[0041] In the zirconia sintered body of this embodiment, for example, the difference in yttria concentration between the crystal grains with the maximum yttria concentration and the crystal grains with the minimum yttria concentration (hereinafter also referred to as "concentration difference between crystal grains") is preferably 2.7 mol% to 7 mol%. Furthermore, when the concentration difference between crystal grains is 3 mol% to 7 mol%, or even 3.2 mol% to 5 mol%, the mechanical strength of the zirconia sintered body tends to be higher.
[0042] Since the mechanical strength tends to be high within the yttria content range of this embodiment, the proportion of the number of crystal grains with an yttria concentration of 3.0 mol% to 4.0 mol% is preferably 10% to 50%. In particular, since the mechanical strength tends to be high, the proportion of the number of crystal grains with an yttria concentration of 3.0 mol% to 4.0 mol% is more preferably 25% to 40%.
[0043] In this embodiment, the yttria concentration of the crystal grains can be obtained by SEM-EDS analysis. Specifically, the yttria concentration of the crystal grains can be obtained by using an SEM observation image observed at a magnification at which the grain boundaries of the crystal grains can be confirmed (for example, a magnification of 10,000 times, preferably a magnification at which the number of crystal grains on the SEM observation image is 150±25), and after identifying the crystal grains, the yttria concentration of each crystal grain that can be confirmed as a whole on the SEM observation image (i.e., crystal grains other than those on the periphery of the SEM observation image) can be obtained by the following formula.
[0044] C=C Y / {C Y +(2×C Zr )}×100 In the above formula, C is the yttria concentration in the crystal grains (mol%), C Y is the total intensity of the EDS spectrum of yttrium in the crystal grain, and C Zr is the total intensity of the EDS spectrum of zirconium in the grain.
[0045] The proportion of the number of crystal grains having an yttria concentration of 3.0 mol% or more and 4.0 mol% or less can be determined from the proportion of the number of crystal grains having an yttria concentration of 3.0 mol% or more and 4.0 mol% or less to the total number of all crystal grains observed (identified) in the above SEM-EDS analysis.
[0046] In this embodiment, the SEM-EDS analysis can be performed using a general SEM-EDS device (for example, SEM: JSM-7600F, manufactured by JEOL Ltd., EDS: NSS312E, manufactured by Thermo Fisher Scientific Inc.). The crystal grains can be identified and quantitative values can be calculated based on the peak intensity of each element in the EDS spectrum using the above-mentioned device or a function (such as an analysis program) installed in the device.
[0047] The zirconia sintered body of this embodiment has a total light transmittance (hereinafter also referred to as "light transmittance") of 46.5% or more, preferably more than 47%, 47.5% or more, or 48% or more, measured according to JIS K 7361-1 with a sample thickness of 1 mm. A zirconia sintered body having a light transmittance lower than this is prevented from being applied to some dental prosthetic materials, such as dental prosthetic materials for anterior teeth. By having a light transmittance of 48.5% or more, preferably 49% or more, the zirconia sintered body of this embodiment is easily applied as a dental prosthetic material that requires particularly high translucency, such as the tip of anterior teeth. The light transmittance of the zirconia sintered body of this embodiment in the range of the yttria content is, for example, 54% or less, 53% or less, or 52% or less.
[0048] In this embodiment, the light transmittance is a total light transmittance measured using daylight as incident light, which can be measured by a method conforming to JIS K 7361-1. In addition, in this embodiment, the linear transmittance is a linear transmittance measured using daylight as incident light, which can be measured by a method conforming to JIS K 7361-1. The light transmittance and linear transmittance can be measured, for example, by using a disk-shaped zirconia sintered body having a sample thickness of 1 mm and a surface roughness Ra≦0.02 μm on both sides as a measurement sample, and using a haze meter equipped with a D65 light source as a measurement device (e.g., haze meter NDH4000, manufactured by Nippon Denshoku Co., Ltd.).
[0049] The zirconia sintered body of this embodiment has a ratio of the integrated value of linear transmittance to the integrated value of total light transmittance (hereinafter also referred to as "PT / TT ratio") of 1.3% or less, preferably 1.2% or less, 1.0% or less, 0.8% or less, or 0.6% or less, at a sample thickness of 1 mm and a measurement wavelength of 400 to 700 nm. The PT / TT ratio is one of the indicators indicating the ratio of linear transmittance to total light transmittance in the visible light range, and by satisfying this range of PT / TT ratio, the zirconia sintered body has translucency with suppressed transparency. As a result, the zirconia sintered body of this embodiment can be visually recognized as a dental prosthetic material with a translucent feeling closer to that of natural teeth. The zirconia sintered body of this embodiment has a PT / TT ratio of more than 0%, preferably 0.1% or more, or 0.3% or more. The range of the PT / TT ratio can be, for example, greater than 0% and not greater than 1.3%, 0.1% or more and not greater than 1.0%, or 0.3% or more and not greater than 0.9%.
[0050] In this embodiment, the PT / TT ratio is obtained by measuring the linear transmittance and the total light transmittance at each wavelength by UV-VIS spectrum measurement, and calculating the ratio of the integrated values. The following conditions are given as the measurement conditions of the UV-VIS spectrum.
[0051] Measurement method: UV-VIS spectrophotometry Measurement method: Double beam method Light source: Halogen lamp Measurement wavelength range: 400nm~700nm Wavelength step: 0.5 nm The PT / TT ratio can be measured, for example, by using a disk-shaped zirconia sintered body having a thickness of 1 mm and a surface roughness on both sides of Ra≦0.02 μm as a measurement sample, and a general UV-VIS spectrophotometer (e.g., Spectrophotometer V-650, manufactured by JASCO Corporation) as a measurement device.
[0052] Since the zirconia sintered body of the present embodiment satisfies the above-mentioned light transmittance and PT / TT ratio, it can also be regarded as a translucent zirconia sintered body, a highly translucent zirconia sintered body, a light-transmitting zirconia sintered body, or the like.
[0053] The zirconia sintered body of this embodiment preferably has a three-point bending strength of 700 MPa or more, 715 MPa or more, 730 MPa or more, or 780 MPa or more. By satisfying such a three-point bending strength, the zirconia sintered body of this embodiment can also be applied as a dental prosthesis of a smaller shape. Furthermore, the three-point bending strength is preferably 800 MPa or more, or 820 MPa or more. By satisfying such a three-point bending strength in addition to the above-mentioned light transmittance and PT / TT ratio, the zirconia sintered body of this embodiment can be applied as a dental prosthesis for anterior teeth as a bridge of four or more. The higher the three-point bending strength, the more preferable it is, but when the yttria content of this embodiment is satisfied, the three-point bending strength can be 1200 MPa or less, 1000 MPa or less, or 900 MPa or less, for example. As the yttria content increases, the three-point bending strength tends to decrease, so for example, when the yttria content is 5.0 mol% or more, the three-point bending strength can be 1000 MPa or less.
[0054] In this embodiment, the three-point bending strength is a value determined by a three-point bending test in accordance with JIS R 1601. The three-point bending strength is measured using a columnar sintered body having a support distance of 30 mm, a width of 4 mm, and a thickness of 3 mm as a measurement sample, and the average value of 10 measurements may be regarded as the three-point bending strength of the zirconia sintered body of this embodiment.
[0055] Furthermore, in the zirconia sintered body of this embodiment, the monoclinic frequency of the fracture source after the three-point bending strength measurement (hereinafter also simply referred to as "monoclinic frequency") is preferably 40% or more or 50% or more, and 80% or less or 75% or less. The monoclinic frequency is a value obtained by microscopic Raman spectroscopy of the optical microscope observation diagram of the fracture source generated by the three-point bending strength measurement, and is the ratio of the number of measurement areas in which the monoclinic ratio (Vm) is 1% or more in the microscopic Raman spectroscopy analysis. Specifically, the optical microscope observation diagram of 900 μm × 600 μm including the fracture source is divided into lattice-shaped measurement areas of 20 μm × 20 μm, the Raman spectrum in each measurement area is measured, and the monoclinic ratio (Vm) is calculated by the following formula.
[0056] Vm = (a × P2) / (b × P1 + a × P2) In the above formula, Vm is the monoclinic ratio and P1 is 149±3 cm -1 The area of the peak with the peak top at 179 ± 3 cm -1 and 189±3 cm -1 is the total area of the peak having a peak top at , and a and b are coefficients (a=0.5 and b=2.2), respectively.
[0057] The monoclinic frequency can be calculated as the ratio of the number of measurement regions having a monoclinic ratio (Vm) of 1% or more to the total number of measurement regions (=1350).
[0058] The micro-Raman spectroscopic analysis can be performed using a general micro-Raman spectroscopic device (e.g., NRS-5100, manufactured by JASCO Corporation), and the peak area of the peak in each measurement region can be determined using analysis software provided with the device (e.g., Spectrum Manager, manufactured by JASCO Corporation).
[0059] The zirconia sintered body of this embodiment has a fracture toughness of 5 MPa m when measured in accordance with the SEPB method specified in JIS R 1607. 1 / 2 and 3MPa m 1 / 2 More than 5MPa m1 / 2 The following can be exemplified.
[0060] The zirconia sintered body of the present embodiment is preferably a sintered body obtained by atmospheric sintering, i.e., a so-called atmospheric sintered body, and more preferably an atmospheric atmospheric sintered body obtained by atmospheric sintering in an atmospheric atmosphere (hereinafter also referred to as "atmospheric sintering"). This makes it easy to manufacture the zirconia sintered body using a sintering furnace that is widely used in the manufacture of dental prosthetic materials.
[0061] The zirconia sintered body of this embodiment is suitable for use as a dental prosthesis, further as a dental prosthesis for anterior teeth, and further as a dental prosthesis for the tip of anterior teeth, among other dental materials. In another embodiment, the zirconia sintered body of this embodiment can also be used as a dental material for dental prosthesis such as crowns, bridges, inlays, onlays, and the like, orthodontic appliances such as orthodontic brackets, and the like. Furthermore, the zirconia sintered body of this embodiment can be applied to other known uses of zirconia sintered bodies, such as structural materials, decorative materials, and optical materials.
[0062] Other embodiments of the zirconia sintered body of the present disclosure include the following.
[0063] A zirconia sintered body comprising yttria and zirconia, the yttria content being 4.5 mol% or more and 6.5 mol% or less, the remainder being zirconia, and comprising crystal grains having different yttria concentrations.
[0064] A zirconia sintered body comprising yttria and zirconia, the yttria content being 4.5 mol% or more and 6.5 mol% or less, the remainder being zirconia, and the proportion of crystal grains having an yttria concentration of 3.0 mol% or more and 4.0 mol% or less among the crystal grains being 10% or more and 50% or less.
[0065] A zirconia sintered body comprising yttria and zirconia, the yttria content being 4.5 mol% or more and 6.5 mol% or less, the remainder being zirconia, and the concentration difference between crystal grains being 3 mol% or more and 7 mol% or less. Contains yttria and zirconia, the yttria content being 4.5 mol% or more and 6.5 mol% or less, with the balance being zirconia; A zirconia sintered body characterized by satisfying at least one of the following: the zirconia sintered body contains crystal grains with different yttria concentrations; the proportion of crystal grains with an yttria concentration of 3.0 mol% or more and 4.0 mol% or less among the crystal grains is 10% or more and 50% or less; and the concentration difference between the crystal grains is 3 mol% or more and 7 mol% or less.
[0066] Next, a method for producing the zirconia sintered body of this embodiment will be described.
[0067] As a preferred method for producing the zirconia sintered body of the present embodiment, a method is provided for producing a zirconia sintered body containing an yttria source and zirconia, the content of the yttria source being 4.5 mol % or more and 6.5 mol % or less, the remainder being zirconia, the total ratio of tetragonal and cubic crystals in the crystal phase of the zirconia being 90% or less, and the BET specific surface area being 7.5 m 2 / g or more 15m 2 and sintering a green compact containing zirconia powder having a molecular weight of 1000 to 2000 g / g or less and an average crystallite size of 325 Å or more.
[0068] The molded body used in the manufacturing method of this embodiment contains an yttria source and zirconia, the content of the yttria source being 4.5 mol % or more and 6.5 mol % or less, the remainder being zirconia, the total ratio of tetragonal and cubic crystals in the crystal phase of the zirconia being 90% or less, and the BET specific surface area being 7.5 m 2 / g or more 15m 2 By subjecting a molded body containing such zirconia powder to sintering, a dense sintered body can be obtained even if a sintering method with a high heating rate during sintering (e.g., 250°C / hour or more) is used or air sintering is used.
[0069] The zirconia powder contains an yttria source and zirconia. The yttria source is at least one of yttria and its precursor, and is preferably yttria. Examples of the yttria precursor include at least one of yttrium chloride and yttrium nitrate, and preferably yttrium chloride. The yttria source is preferably solid-dissolved in zirconia, and all of the yttria source may be solid-dissolved in zirconia, and the zirconia powder preferably does not contain an yttria source that is not solid-dissolved in zirconia.
[0070] The content of the yttria source may be equal to the yttria content in the desired zirconia sintered body. The content of the yttria source in the zirconia powder may be, for example, 4.5 mol% to 6.5 mol%, more than 4.5 mol% to 6.0 mol%, 4.7 mol% to 5.8 mol%, or 4.8 mol% to 5.5 mol%. In another embodiment, the content of the yttria source may be, for example, 5.0 mol% to 6.0 mol%, or 5.0 mol% to 5.8 mol%.
[0071] The content of the yttria source in the zirconia powder is the percentage (mol%) of yttrium (Y) converted to Y2O3 relative to the total value of zirconium (Zr) in the zirconia powder converted to ZrO2 and yttrium (Y) converted to Y2O3, and is calculated by {Y2O3 [mol] / (ZrO2+Y2O3) [mol]}×100.
[0072] The zirconia powder may contain an alumina source. The alumina source is at least one of alumina and its precursor, preferably alumina, and more preferably α-alumina. The content of the alumina source in the zirconia powder may be the same as the alumina content in the target zirconia sintered body. The content of the alumina source in the zirconia powder may be 0% by mass or more and 0.2% by mass or less, 0% by mass or more and 0.15% by mass or less, 0% by mass or more and less than 0.1% by mass, more than 0% by mass and 0.2% by mass or less, 0.005% by mass or more and 0.15% by mass or less, 0.01% by mass or more and 0.12% by mass or less, or 0.015% by mass or more and less than 0.1% by mass.
[0073] The content of the alumina source in the zirconia powder is the mass ratio (mass%) of aluminum (Al) converted to Al2O3 relative to the total mass of zirconium (Zr) converted to ZrO2, yttrium (Y) converted to Y2O3, and aluminum (Al) converted to Al2O3 in the zirconia powder, and is calculated from {Al2O3 [g] / (ZrO2+Y2O3+Al2O3) [g]}×100.
[0074] The zirconia powder may contain a colorant to give the desired color tone to the desired zirconia sintered body. The colorant may be an element having a function of coloring zirconia and a function of suppressing the phase transition of zirconia. Specific examples of the colorant include at least one of transition metal elements and lanthanoid rare earth elements, preferably at least one selected from the group consisting of iron, cobalt, nickel, manganese, praseodymium, neodymium, europium, gadolinium, terbium, erbium, and ytterbium, more preferably at least one selected from the group consisting of iron, cobalt, manganese, praseodymium, neodymium, terbium, and erbium, and even more preferably at least one selected from the group consisting of iron, cobalt, and erbium.
[0075] The zirconia powder may contain inevitable impurities such as hafnia (HfO2). The content of hafnia as an inevitable impurity is 2.0 mass% or less. However, the zirconia powder satisfies at least one of the following: the content of magnesium calculated as magnesia (MgO) is 0 mass ppm or more and 500 mass ppm or less, the content of silicon calculated as silica (SiO2) is 0 mass ppm or more and 500 mass ppm or less, and the content of titanium calculated as titania (TiO2) is 0 mass ppm or more and 500 mass ppm or less, and it is preferable that the contents of magnesium, silicon, and titanium are each 0 mass ppm or more and 500 mass ppm or less.
[0076] The total ratio of tetragonal and cubic crystals in the crystal phase of the zirconia powder (hereinafter also referred to as "T+C phase ratio") is 90% or less, and preferably 85% or less, 80% or less, or 75% or less. By satisfying this range of the T+C phase ratio and the average crystallite size described below, the mechanical strength of the zirconia sintered body obtained after sintering is high. The T+C phase ratio is preferably 50% or more, 55% or more, or 60% or more. In this embodiment, phases other than the T+C phase ratio in the crystal phase of the zirconia powder may be regarded as monoclinic. The ratio of monoclinic crystals in the crystal phase (hereinafter also referred to as "M phase ratio") may be more than 10%, more than 15%, more than 20%, or more than 25%, and may be less than 50%, less than 45%, or less than 40%. In addition, when the yttria content is high, the T+C phase ratio is also likely to be high.
[0077] The T+C phase ratio in zirconia powder is the tetragonal + cubic phase ratio (f T+C ), the M phase rate can be obtained by the same method as the monoclinic phase rate (f M The XRD pattern of the zirconia powder can be obtained by measuring the zirconia powder under the same conditions as those for the XRD measurement of the zirconia sintered body.
[0078] The zirconia powder has a BET specific surface area of 7.5m 2 / g or more 15m 2 / g or less. In the above-mentioned content of the yttria source, if the BET specific surface area is less than this range, the sintering rate becomes too slow, while if the BET specific surface area exceeds this range, the sintering rate becomes too fast. In either case, densification becomes difficult in normal pressure sintering, particularly in air sintering. Even when sintering with a high heating rate is applied, there is a tendency for densification to be promoted, so the BET specific surface area is preferably 8 m 2 / g or more 15m 2 / g or less, 9m 2 / g or more 13m 2 / g or less, or 9.5m 2 / g or more 11m 2 In another embodiment, the BET specific surface area is 9.5 m 2 / g or more or 10m 2 / g or more, and 12m 2 / g or less, 11m 2 / g or less or 10.5m 2 / g or less.
[0079] In this embodiment, the BET specific surface area is a BET specific surface area measured in accordance with JIS Z 8830, and may be measured by a BET single-point method using a carrier gas method in which nitrogen is used as an adsorption gas. Specific measurement conditions for the BET specific surface area include the following conditions.
[0080] Adsorption medium: N2 Adsorption temperature: -196℃ Pretreatment conditions: Treatment in air at 250℃ for 30 minutes The BET specific surface area can be measured using a common device (for example, FlowSorb III2305, manufactured by Shimadzu Corporation).
[0081] The zirconia powder has an average crystallite diameter of 325 Å or more, preferably 330 Å or more, 335 Å or more, or 340 Å or more. In addition to the above T+C phase ratio, zirconia powder that satisfies this range of average crystallite diameter is likely to efficiently promote the growth of crystal grains and the elimination of pores during sintering, and a zirconia sintered body having high translucency and mechanical strength can be obtained even by normal pressure sintering or even air sintering. For the same reason, the average crystallite diameter is preferably 450 Å or less, 400 Å or less, 398 Å or less, or 380 Å or less. Note that the higher the yttria content, the larger the average crystallite diameter tends to be.
[0082] In this embodiment, the average crystallite diameter is a crystallite diameter determined from an XRD peak (hereinafter also referred to as the "main XRD peak") where the tetragonal (111) plane and the cubic (111) plane overlap in the XRD pattern of the zirconia powder, and is a value calculated from the following formula.
[0083] D = κλ / βcosθ In the above formula, D is the average crystallite size (Å), κ is the Scherrer constant (κ=1), λ is the wavelength of the measured X-ray (when CuKα radiation is used as the radiation source, λ=0.15418 nm), β is the half-width of the main XRD peak (°), and θ is the Bragg angle of the main XRD peak. Note that β is the half-width of the main XRD peak obtained by profile fitting the XRD pattern after smoothing and background removal using a split pseudo-Voigt function. Profile fitting can be performed using an analysis program attached to the X-ray diffraction device (for example, integrated powder X-ray analysis software PDXL Ver.2.2, manufactured by RIGAKU Corporation).
[0084] The average particle size of the zirconia powder is preferably 0.35 μm or more and 0.5 μm or less, and more preferably 0.4 μm or more and 0.45 μm or less.
[0085] In this embodiment, the average particle size is D50 in the volume particle size distribution of the powder measured by the wet method, and can be measured using a general device (e.g., MT3300EXII, manufactured by Microtrack Bell). As a measurement sample, a powder from which slow aggregation has been removed by a dispersion treatment such as ultrasonic treatment is dispersed in pure water to form a slurry. The measurement of the volume particle size distribution by the wet method is preferably performed by making the slurry acidic (e.g., pH=3.0 to 6.0).
[0086] The method for producing the zirconia powder is arbitrary, and an example thereof includes a production method including a step of heat-treating a composition containing a zirconia sol and an yttria source at 950°C to 1250°C, and then pulverizing the composition. The zirconia sol is preferably a zirconia sol obtained by either a hydrothermal synthesis method or a hydrolysis method, and more preferably a zirconia sol obtained by a hydrolysis method. The higher the heat treatment temperature, the smaller the BET specific surface area tends to be, and the heat treatment temperature may be set according to the desired BET specific surface area.
[0087] In order to improve the handling of the zirconia powder, the zirconia powder may be a granulated powder (hereinafter, also referred to as "powder granules"). The powder granules may have a granule diameter of 30 μm or more and 80 μm or less. Granulation may be performed by any method that results in a slow aggregation of the zirconia powder, and examples of such methods include granulation methods such as spray granulation.
[0088] In this embodiment, the granule particle size is D50 in the volumetric particle size distribution of the powder measured by a dry method, and can be measured using a general device (e.g., MT3100II, manufactured by Microtrack Bell Co., Ltd.). As the measurement sample, the powder in a slowly aggregated state may be used as it is without being subjected to a dispersion treatment such as ultrasonic treatment.
[0089] The zirconia powder preferably contains zirconia powder particles having different yttria contents, and more preferably contains zirconia powder particles having a certain yttria content and zirconia powder particles having a different yttria content from the zirconia powder particles (hereinafter, in the zirconia powder, zirconia powder particles having a high yttria content are also referred to as "high Y particles", and zirconia powder particles having a lower yttria content compared to the high Y particles are also referred to as "low Y particles".) This tends to increase the translucency of the obtained zirconia sintered body even when sintered at a relatively low sintering temperature.
[0090] In this embodiment, "containing zirconia powder particles having different yttria contents" means that the yttria contents of some of the zirconia powder particles constituting the zirconia powder are different from each other, and it is not necessary that the yttria contents of all of the zirconia powder particles constituting the zirconia powder are different from each other.
[0091] In another embodiment, the zirconia powder preferably includes two or more zirconia powder particles, and the yttria content of the first zirconia powder particles is different from the yttria content of the second zirconia powder particles. In yet another embodiment, the zirconia powder is preferably a mixed powder of a zirconia powder having a certain yttria content and a zirconia powder having a different yttria content from the zirconia powder.
[0092] The yttria content of the low Y particles is, for example, 1.0 mol% or more, 1.3 mol% or more, 1.5 mol% or more, 1.8 mol% or more, 2.0 mol% or more, or 2.3 mol% or more, and 5.0 mol% or less, 4.5 mol% or less, 4.2 mol% or less, 3.5 mol% or less, or 3.2 mol% or less. The yttria content of the high Y particles is, for example, more than 5.0 mol%, 5.2 mol% or more, 5.5 mol% or more, or 6.0 mol% or more, and 10.0 mol% or less, 9.0 mol% or less, 8.5 mol% or less, 8.0 mol% or less, or 7.0 mol% or less.
[0093] The difference in yttria content between the high Y particles and the low Y particles (hereinafter also referred to as "yttria content difference") is preferably more than 3.0 mol%. This makes it easier for the zirconia powder to satisfy the above-mentioned T+C phase ratio and average crystallite size. The yttria content difference is preferably 3.3 mol% or more, 3.5 mol% or more, 4.0 mol% or more, or 4.3 mol% or more. The yttria content difference can be, for example, 7.5 mol% or less, 7.0 mol% or less, or 6.5 mol% or less. Since the zirconia sintered body obtained by sintering in an air atmosphere tends to have high translucency and mechanical strength, the yttria content difference is preferably 3.8 mol% or more and 6.5 mol% or less.
[0094] In this embodiment, the difference in yttria content can be measured by STEM-EDS of the zirconia powder. In another embodiment, if the manufacturing method of the zirconia powder is known, it can be determined from the difference in yttria content of each precursor powder used in the manufacturing.
[0095] In the STEM-EDS measurement of zirconia powder, an electron beam is irradiated onto powder particles that are observed without overlapping with each other in a TEM observation image, and an EDS spectrum of each zirconia powder particle is obtained. For the obtained EDS spectrum, the yttria content of each powder particle (=Y2O3 / (ZrO2+Y2O3):mol%) can be measured from the yttrium peak intensity relative to the total of the yttrium peak intensity and the zirconium peak intensity.
[0096] In STEM-EDS measurement, the yttria concentration of a sufficient number of zirconia powder particles (for example, 10 or more, preferably 30±5) is obtained, and the difference between the maximum and minimum values is taken as the yttria concentration difference.
[0097] In this embodiment, the STEM-EDS measurement can be performed, for example, by using a commercially available device (for example, TEM: JEM-2100F, manufactured by JEOL Ltd., EDS: JED-2300T, manufactured by JEOL Ltd.).
[0098] Preferably, the T+C phase ratio of the low Y particles is, for example, 0% or more or 1% or more, and 50% or less, 40% or less, 20% or less, or 10% or less, and the T+C phase ratio of the high Y particles is, for example, more than 50%, 70% or more, or 90% or more, and 100% or less.
[0099] The method for producing the zirconia powder containing zirconia powder particles with different yttria contents is arbitrary, and it is preferable to mix two or more zirconia powders with different yttria contents (hereinafter, each of them is also referred to as "precursor powders") so as to obtain the physical properties of the zirconia powder to be used in the production method of this embodiment. In this way, a zirconia powder consisting of a mixed powder is obtained. The mixing method may be any method that sufficiently mixes the precursor powders, and examples thereof include at least one of dry mixing and wet mixing, with wet mixing being preferred, and mixing in an aqueous solvent being more preferred.
[0100] The mixing ratio of the precursor powders may be appropriately adjusted depending on the yttria content of the precursor powder and the target zirconia powder, and may be 1 mass%:99 to 99 mass%:1 mass%, 20 mass%:80 to 80 mass%:20 mass%, or 35 mass%:65 to 65 mass%:35 mass%. The zirconia powder may be a mixed powder of two types of precursor powders, but may also be a mixed powder of three or more types of precursor powders.
[0101] From the viewpoint of homogenizing the physical properties of the zirconia powder, it is preferable that the precursor powders have a BET specific surface area and average particle size comparable to those of the target zirconia powder, and it is sufficient that the precursor powders have the BET specific surface area and average particle size values of the zirconia powder described above. It is preferable that the high yttria powder has a larger BET specific surface area than the low yttria powder (for example, the difference in BET specific surface area is 0.5 m). 2 / g or more 2.0m 2 / g or less).
[0102] The molded body may contain a binder. By containing a binder, the shape retention of the molded body is improved. The binder contained in the molded body can be a known one used for molding ceramics, and is preferably an organic binder. The organic binder is one or more selected from the group of polyvinyl alcohol, polyvinyl butyrate, wax, and acrylic resin, preferably one or more of polyvinyl alcohol and acrylic resin, more preferably acrylic resin. In this embodiment, the acrylic resin is a polymer containing at least one of acrylic acid ester and methacrylic acid ester. Specific examples of the acrylic resin include one or more selected from the group of polyacrylic acid, polymethacrylic acid, acrylic acid copolymer, and methacrylic acid copolymer, and derivatives thereof.
[0103] The shape of the molded body used in the manufacturing method of this embodiment is arbitrary. Examples of the shape of the molded body include at least one selected from the group consisting of a cube, a rectangular parallelepiped, a polyhedron, a columnar, a cylindrical, a disk, and a substantially spherical shape, and a shape similar to the target zirconia sintered body, such as a dental prosthesis shape, taking into account thermal shrinkage due to sintering.
[0104] The relative density of the molded body is, for example, 45% or more and 55% or less, and preferably 48% or more and 52% or less.
[0105] The relative density of a molded body is the ratio of the measured density to the theoretical density. The measured density is the density (g / cm3) calculated by the mass measured by mass measurement relative to the volume calculated by the dimensions measured by size measurement. 3 ) and the measurement can be performed in the same manner as for the zirconia sintered body.
[0106] The method for manufacturing the molded body used in the manufacturing method of this embodiment is arbitrary, and known ceramic molding methods can be applied. As the molding method, for example, one or more selected from the group consisting of uniaxial pressing, cold isostatic pressing, slip casting, and injection molding can be exemplified. Since it is simple, the molding method is preferably at least one of uniaxial pressing and cold isostatic pressing, and it is more preferable to perform cold isostatic pressing after uniaxial pressing. This results in a molded body, that is, a green compact that maintains the shape in which the zirconia powder is physically aggregated. The pressure of the uniaxial pressing can be 15 MPa or more and 150 MPa or less, and the pressure of the cold isostatic pressing can be 90 MPa or more and 400 MPa or less, and the higher the pressure in molding, the higher the density of the obtained molded body tends to be. The molded body obtained by such a manufacturing method can also be considered as a green compact containing zirconia powder.
[0107] When the molded body contains a binder, a step of removing the binder, i.e., a so-called binder removal step, may be carried out prior to sintering. Any method for removing the binder may be used, but a heat treatment at 400 to less than 900°C in air may be exemplified.
[0108] In the step of sintering the above-mentioned molded body (hereinafter also referred to as the "sintering step"), the molded body may be a molded body having a structure at the initial stage of sintering, that is, a so-called calcined body. An example of the structure at the initial stage of sintering is a structure in which zirconia particles form a necking, and the calcined body may be composed of fused particles of zirconia. The calcined body can be formed into any shape by processing such as CAD / CAM, which makes it easier to obtain a zirconia sintered body of any shape.
[0109] The calcination conditions include heat treatment at a temperature below the sintering temperature of zirconia, for example, in an air atmosphere at 900°C or higher and lower than 1200°C for 0.5 hours or longer and 10 hours or shorter, preferably in an air atmosphere at 1000°C or higher and 1150°C or lower for 1 hour or longer and 10 hours or shorter.
[0110] The calcined body is obtained by forming a zirconia powder into a compact, which is then heat-treated. Since the BET specific surface area, T+C phase ratio, crystallite size, etc. change with heat treatment, the physical properties of the formed body (compressed powder) and the calcined body often do not match. Examples of the calcined body include a calcined body containing an yttria source and zirconia, with the yttria source content being 4.5 mol% to 6.5 mol% and the balance being zirconia, and further a calcined body containing an yttria source content being 4.5 mol% to 6.5 mol% and the balance being zirconia, and composed of fused particles.
[0111] The calcined body obtained by the manufacturing method of this embodiment may have a maximum frequency (hereinafter also referred to as "maximum frequency") of the distribution of yttrium concentration in quantitative elemental analysis of energy dispersive spectrum of less than 30%, 28% or less, or 15% or less. Also, the maximum frequency may be, for example, 8% or more, or 10% or more.
[0112] In addition, the calcined body may have a difference between the maximum and minimum yttria concentrations in quantitative elemental analysis of an energy dispersive spectrum of more than 3.0 mol%, 3.3 mol% or more, 3.5 mol% or more, 4.0 mol% or more, or 4.3 mol% or more, and may have a difference of 7.5 mol% or less, 7.0 mol% or less, or 6.5 mol% or less.
[0113] The quantitative analysis of elements in the energy dispersive spectrum (hereinafter also referred to as "EDS spectrum") may be performed by obtaining an EDS spectrum for a scanning electron microscope (hereinafter also referred to as "SEM") observation image of the calcined body, and quantifying the intensities of characteristic X-rays of zirconium (Zr) and yttrium (Y) in the obtained EDS spectrum. The quantitative analysis of the EDS spectrum may be performed for 40,000 points or more (preferably 50,000±10,000 points) in the SEM observation image. The yttrium concentration may be determined as the ratio of the intensity of yttrium to the intensity of zirconium (hereinafter also referred to as "Y / Zr ratio"). The yttrium concentration distribution may be an yttrium concentration distribution shown by dividing a certain yttrium concentration into a concentration range, and may be an yttrium concentration distribution shown by dividing the Y / Zr ratio into a concentration range of 0.5 atomic percent. The frequency is the ratio (%) of the number of measurement points corresponding to each yttrium concentration to the total number of measurement points in the quantitative analysis of the EDS spectrum.
[0114] The sintering in the sintering step can be performed by a known sintering method, for example, one or more selected from the group consisting of atmospheric sintering, pressure sintering, and vacuum sintering. However, since it is widely applied to the production of dental prosthetic materials, the sintering method is preferably atmospheric sintering, and more preferably, only atmospheric sintering, that is, a sintering method that does not use pressure sintering or vacuum sintering. From the molded body subjected to the manufacturing method of this embodiment, even if the sintering method is only atmospheric sintering, the zirconia sintered body of this embodiment can be obtained as a so-called atmospheric sintered body. In this embodiment, "atmospheric sintering" refers to a method of sintering by heating the sintered object (such as a molded body or a calcined body) without applying an external force during sintering.
[0115] Examples of sintering conditions include the following conditions. The sintering temperature is 1200°C or more and 1600°C or less, preferably 1300°C or more and 1580°C or less, 1400°C or more and 1560°C or less, or 1430°C or more and 1560°C or less. In another embodiment, the sintering temperature is 1450°C or more and 1650°C or less, preferably 1500°C or more and 1650°C or less, or 1550°C or more and 1650°C or less. The heating rate up to the sintering temperature can be 50°C / hour or more and 800°C / hour or less, preferably 100°C / hour or more and 800°C / hour or less, 150°C / hour or more and 800°C / hour or less, or 150°C / hour or more and 700°C / hour or less. The holding time at the sintering temperature (hereinafter also referred to as "sintering time") varies depending on the sintering temperature, but is 1 hour or more and 5 hours or less, 1 hour or more and 3 hours or less, or 1 hour or more and 2 hours or less. The sintering atmosphere is preferably an atmosphere other than a reducing atmosphere, and more preferably at least one of an oxygen atmosphere and an air atmosphere. Sintering in an oxygen atmosphere tends to promote pore elimination, and the linear transmittance of the obtained zirconia sintered body may become too high. Therefore, the sintering atmosphere is more preferably an air atmosphere. The air atmosphere is, for example, an atmosphere mainly composed of nitrogen and oxygen, with an oxygen concentration of about 18 to 23 volume %. EXAMPLES
[0116] The present embodiment will be specifically described below with reference to examples, but the present embodiment is not limited to these examples.
[0117] (XRD measurement) The XRD patterns of the powder sample and the sintered body sample were obtained by XRD measurement under the following conditions. Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ=26°~33°
[0118] A general X-ray diffraction device (device name: MiniFlex, manufactured by RIGAKU) was used for the XRD measurement. The analysis program attached to the device (software name: Integrated Powder X-ray Analysis Software PDXL Ver.2.2, manufactured by RIGAKU) was used. The obtained XRD pattern was smoothed and background processed, and then analyzed by profile fitting using a split pseudo-Voigt function. Note that since the average crystallite diameter of zirconia powder is small and the effect of the mechanical spread of the XRD device on the calculation is small, the β value was calculated without correcting for the mechanical spread.
[0119] (composition analysis) The composition of the samples was determined by ICP analysis.
[0120] (BET specific surface area) The BET specific surface area of the powder sample was measured using a flow-type automatic specific surface area measuring device (Device name: FlowSorb III2305, Shimadzu Corporation) using nitrogen as the adsorption gas. Prior to the measurement of the BET specific surface area, the powder sample was degassed in air at 250°C for 30 minutes.
[0121] (Average particle size) The average particle size of the powder samples was measured using a Microtrack particle size distribution analyzer (device name: MT3300EXII, manufactured by Microtrack Bell).
[0122] As a pretreatment, the sample powder was suspended in distilled water to form a slurry, which was then dispersed for 3 minutes using an ultrasonic homogenizer (device name: US-150T, manufactured by Nippon Seiki Seisakusho).
[0123] (Average grain size) The average crystal grain size of the zirconia sintered body was determined by the planimetric method using SEM observation images. As a measurement sample, a zirconia sintered body with a surface roughness of Ra≦0.02 μm was used, which was treated in air at a temperature 50°C lower than the sintering temperature, and observed with an SEM at a magnification (5000 to 10000 times) at which about 200 crystal grains could be observed.
[0124] A circle of known area was drawn on the obtained SEM observation diagram, and the number of crystal grains within the circle (Nc) and the number of crystal grains on the circumference of the circle (Ni) were measured. The total number of crystal grains (Nc+Ni) was set to 250±50, and the average crystal grain size was calculated using the following formula. Average grain size=2 / {π×(Nc+(1 / 2)×Ni) / (A / M 2 )} 0.5
[0125] (Relative Density) The relative density of the sintered samples was calculated as the ratio (%) of the measured density to the theoretical density. The measured density is the ratio (g / cm) of the volume measured by the Archimedes method to the mass measured using an electronic balance. 3 The theoretical density was calculated from the above formulas (1) to (4).
[0126] (Light transmittance and linear transmittance) The light transmittance (total light transmittance) and linear transmittance were measured using a haze meter (device name: NDH4000, manufactured by Nippon Denshoku Industries Co., Ltd.) with a D65 light source according to a method in accordance with JIS K 7361-1.
[0127] The measurement sample used was a disk-shaped sintered body having a thickness of 1 mm and having a surface roughness of Ra≦0.02 μm and polished on both sides.
[0128] (PT / TT ratio) The PT / TT ratio was measured using a disk-shaped zirconia sintered body having a thickness of 1 mm and a surface roughness on both sides of Ra≦0.02 μm as a measurement sample, and a general UV-VIS spectrophotometer (e.g., Spectrophotometer V-650, manufactured by JASCO Corporation) as a measurement device. The measurement conditions are as follows.
[0129] Measurement method: UV-VIS spectrophotometry Measurement method: Double beam method Light source: Halogen lamp Measurement wavelength range: 400nm~700nm Wavelength step: 0.5 nm (Three-point bending strength) The three-point bending strength was measured according to the method of JIS R 1601. The measurement was performed 10 times and the average value was calculated. The measurement was performed on a columnar sintered body sample with a width of 4 mm and a thickness of 3 mm, with a support distance of 30 mm. The crosshead speed was 0.5 mm / min.
[0130] Example 1 A hydrated zirconia sol obtained by hydrolyzing an aqueous solution of zirconium oxychloride was mixed with yttria and dried, and then heat-treated in air at 1160°C for 2 hours to obtain an yttria-containing zirconia powder with an yttria content of 2.5 mol%. The obtained yttria-containing zirconia powder, α-alumina with an average particle size of 0.3 μm, and pure water were mixed to obtain a slurry containing zirconia powder (precursor powder 1) containing 0.05 mass% alumina and containing 2.5 mol% yttria. The obtained zirconia powder (precursor powder 1) had a T+C phase ratio of 18%, an average crystallite size of 196 Å, and a BET specific surface area of 10.0 m 2 / g.
[0131] In addition, a slurry containing zirconia powder (precursor powder 2) containing 0.05 mass% alumina and 8.5 mol% yttria was obtained by the same method except that the yttria content was 8.5 mol%. The obtained zirconia powder (precursor powder 2) had a T+C phase ratio of 100%, an average crystallite diameter of 397 Å, and a BET specific surface area of 11.3 m 2 / g.
[0132] The difference in yttria content between the slurry of Precursor Powder 1 and the slurry of Precursor Powder 2 was 6.0 mol%. The two slurries were mixed so that the yttria content was 5.2 mol%, and then dried to obtain a zirconia powder containing 0.05 mass% alumina and having an yttria content of 5.2 mol%.
[0133] Zirconia powder was uniaxially press molded at a pressure of 19.6 MPa and subjected to CIP treatment at a pressure of 196 MPa to obtain a green body.
[0134] The obtained compact was calcined at 1000°C for 1 hour in an air atmosphere to obtain a calcined body. The calcined body had a maximum frequency of 12%, and the difference between the maximum and minimum values of the yttria concentration was 5.5mol%. Then, the calcined body was sintered at a heating rate of 600°C / hour and a sintering temperature of 1450°C for 2 hours in an air atmosphere to obtain the zirconia sintered body of this example.
[0135] Example 2 A slurry containing zirconia powder (precursor powder 1) containing 0.05 mass% alumina and 2.0 mol% yttria was prepared in the same manner as in precursor powder 1 of Example 1, except that yttria was mixed so that the yttria content was 2.0 mol%. The obtained zirconia powder (precursor powder 1) had a T+C phase ratio of 4%, an average crystallite diameter of 169 Å, and a BET specific surface area of 8.6 m 2 / g.
[0136] A slurry containing zirconia powder (precursor powder 2) containing 0.05 mass% alumina and 6.5 mol% yttria was prepared in the same manner as in precursor powder 2 of Example 1, except that yttria was mixed so that the yttria content was 6.5 mol%. The obtained zirconia powder (precursor powder 2) had a T+C phase ratio of 100%, an average crystallite diameter of 350 Å, and a BET specific surface area of 10.3 m 2 / g.
[0137] The difference in yttria content between the slurry of Precursor Powder 1 and the slurry of Precursor Powder 2 was 4.5 mol %. Both slurries were mixed so that the yttria content was 5.2 mol %, and then dried to obtain a zirconia powder containing 0.05 mass % alumina and having an yttria content of 5.2 mol %.
[0138] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example.
[0139] Example 3 A slurry containing zirconia powder (precursor powder 1) containing 0.05 mass% alumina and 1.5 mol% yttria was prepared in the same manner as in precursor powder 1 of Example 1, except that yttria was mixed so that the yttria content was 1.5 mol%. The obtained zirconia powder (precursor powder 1) had a T+C phase ratio of 0% and a BET specific surface area of 7.9 m 2 / g.
[0140] A slurry containing zirconia powder (precursor powder 2) containing 0.05 mass % of alumina and 8.5 mol % of yttria was obtained by a method similar to that for precursor powder 2 in Example 1.
[0141] The difference in yttria content between the slurry of Precursor Powder 1 and the slurry of Precursor Powder 2 was 7.0 mol %. Both slurries were mixed so that the yttria content was 5.2 mol %, and then dried to obtain a zirconia powder containing 0.05 mass % alumina and having an yttria content of 5.2 mol %.
[0142] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example.
[0143] Example 4 A slurry containing zirconia powder (precursor powder 1) containing 0.05 mass% alumina and 1.5 mol% yttria was prepared in the same manner as precursor powder 1 in Example 1, except that yttria was mixed so that the yttria content was 1.5 mol% and heat treatment was performed in air at 1130°C for 2 hours. The obtained zirconia powder had a T+C phase ratio of 0% and a BET specific surface area of 11.4 m. 2 / g.
[0144] A slurry containing zirconia powder (precursor powder 2) containing 0.05 mass% alumina and 5.5 mol% yttria was prepared in the same manner as in precursor powder 2 of Example 1, except that yttria was mixed so that the yttria content was 5.5 mol%. The obtained zirconia powder had a T+C phase ratio of 97%, an average crystallite diameter of 340 Å, and a BET specific surface area of 10.0 m 2 / g.
[0145] The difference in yttria content between the slurry of Precursor Powder 1 and the slurry of Precursor Powder 2 was 4.0 mol %. Both slurries were mixed so that the yttria content was 5.2 mol %, and then dried to obtain a zirconia powder containing 0.05 mass % alumina and having an yttria content of 5.2 mol %.
[0146] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example. The obtained calcined body had a maximum frequency of 26%, and the difference between the maximum and minimum values of the yttria concentration was 3.3 mol%.
[0147] Example 5 A slurry containing zirconia powder (precursor powder 1) containing 0.05 mass% alumina and 3.0 mol% yttria was prepared in the same manner as in precursor powder 1 of Example 1, except that yttria was mixed so that the yttria content was 3.0 mol%. The obtained zirconia powder had a T+C phase ratio of 42%, an average crystallite diameter of 236 Å, and a BET specific surface area of 9.5 m 2 / g.
[0148] A slurry containing zirconia powder (precursor powder 2) containing 0.05 mass% alumina and 6.5 mol% yttria was prepared in the same manner as in precursor powder 2 of Example 1, except that yttria was mixed so that the yttria content was 6.5 mol%. The obtained zirconia powder had a T+C phase ratio of 100%, an average crystallite diameter of 350 Å, and a BET specific surface area of 10.3 m 2 / g.
[0149] The difference in yttria content between the slurry of Precursor Powder 1 and the slurry of Precursor Powder 2 was 3.5 mol %. Both slurries were mixed so that the yttria content was 5.2 mol %, and then dried to obtain a zirconia powder containing 0.05 mass % alumina and having an yttria content of 5.2 mol %.
[0150] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example.
[0151] Example 6 A slurry containing zirconia powder (precursor powder 1) containing 0.05 mass% alumina and 2.5 mol% yttria was prepared in the same manner as in precursor powder 1 of Example 1, except that yttria was mixed so that the yttria content was 2.5 mol%. The obtained zirconia powder (precursor powder 1) had a BET specific surface area of 9.1 m 2 / g.
[0152] A slurry containing zirconia powder (precursor powder 2) containing 0.05 mass% alumina and 8.5 mol% yttria was prepared in the same manner as in precursor powder 2 of Example 1, except that yttria was mixed so that the yttria content was 8.5 mol%. The obtained zirconia powder had a BET specific surface area of 11.3 m 2 / g.
[0153] The difference in yttria content between the slurry of Precursor Powder 1 and the slurry of Precursor Powder 2 was 6.0 mol%. Both slurries were mixed so that the yttria content was 5.5 mol%, and then dried to obtain a zirconia powder containing 0.05 mass% alumina and having an yttria content of 5.5 mol%.
[0154] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example.
[0155] Example 7 A slurry containing zirconia powder (precursor powder 1) containing 0.05 mass% alumina and 2.5 mol% yttria was prepared in the same manner as precursor powder 1 in Example 1, except that yttria was mixed so that the yttria content was 2.5 mol% and heat treatment was performed in air at 1160°C for 2 hours. The obtained zirconia powder had a BET specific surface area of 10.0 m 2 / g.
[0156] A slurry containing zirconia powder (precursor powder 2) containing 0.05 mass% alumina and 8.5 mol% yttria was prepared in the same manner as in precursor powder 2 of Example 1, except that yttria was mixed so that the yttria content was 8.5 mol%. The obtained zirconia powder had a BET specific surface area of 11.3 m 2 / g.
[0157] The difference in yttria content between the slurry of Precursor Powder 1 and the slurry of Precursor Powder 2 was 6.0 mol%. Both slurries were mixed so that the yttria content was 5.5 mol%, and then dried to obtain a zirconia powder containing 0.05 mass% alumina and having an yttria content of 5.5 mol%.
[0158] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example.
[0159] Example 8 A slurry containing zirconia powder (precursor powder 1) containing 0.05 mass% alumina and 1.5 mol% yttria was prepared in the same manner as precursor powder 1 in Example 1, except that yttria was mixed so that the yttria content was 1.5 mol% and heat treatment was performed in air at 1150°C for 2 hours. The obtained zirconia powder had a T+C phase ratio of 0% and a BET specific surface area of 10.7 m. 2 / g. In addition, a slurry containing precursor powder 2 was obtained in the same manner as in Example 4.
[0160] The difference in yttria content between the slurry of Precursor Powder 1 and the slurry of Precursor Powder 2 was 4.0 mol%. Both slurries were mixed so that the yttria content was 4.8 mol%, and then dried to obtain a zirconia powder containing 0.05 mass% alumina and an yttria content of 4.8 mol%.
[0161] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example.
[0162] Example 9 A zirconia powder containing 0.05 mass% alumina and an yttria content of 5.0 mol% was obtained in the same manner as in Example 8, except that a slurry of precursor powder 1 and a slurry of precursor powder 2 were mixed so that the yttria content was 5.0 mol%.
[0163] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example.
[0164] Example 10 A zirconia powder containing 0.05 mass% alumina and an yttria content of 5.8 mol% was obtained in the same manner as in Example 1, except that a slurry of precursor powder 1 and a slurry of precursor powder 2 were mixed so that the yttria content was 5.8 mol%.
[0165] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example.
[0166] Example 11 A slurry containing zirconia powder (precursor powder 1) with an yttria content of 2.5 mol% was obtained by the same method as for precursor powder 1 in Example 1, except that the heat treatment was performed in air at 1,140°C for 2 hours and alumina was not used. The obtained zirconia powder (precursor powder 1) had a T+C phase ratio of 17% and a BET specific surface area of 11.1 m. 2 / g. A slurry containing zirconia powder (precursor powder 2) containing 0.05 mass % of alumina and 8.5 mol % of yttria was obtained by a method similar to that for precursor powder 2 in Example 1.
[0167] In the same manner as in Example 1, a slurry of precursor powder 1 and a slurry of precursor powder 2 were mixed to obtain a zirconia powder containing 0.023 mass % of alumina and having an yttria content of 5.2 mol %.
[0168] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example.
[0169] Example 12 A slurry containing zirconia powder (precursor powder 1) with an yttria content of 2.0 mol% was prepared in the same manner as precursor powder 1 in Example 1, except that yttria was mixed so that the yttria content was 2.0 mol%, heat treatment was performed in air at 1160°C for 2 hours, and alumina was not used. The obtained zirconia powder (precursor powder 1) had a T+C phase ratio of 5% and a BET specific surface area of 10.2 m 2 / g.
[0170] A slurry containing zirconia powder (precursor powder 2) with an yttria content of 8.5 mol% was prepared in the same manner as in Precursor Powder 2 of Example 1, except that the heat treatment was performed in air at 1,130°C for 2 hours and that no alumina was used. The obtained zirconia powder (precursor powder 2) had a BET specific surface area of 12.4 m 2 / g.
[0171] The difference in yttria content between the slurry of precursor powder 1 and the slurry of precursor powder 2 was 6.5 mol%. The slurries of precursor powder 1 and 2 were mixed in the same manner as in Example 1 to obtain a zirconia powder containing no alumina (alumina content: 0 mass%) and containing yttria of 5.2 mol%.
[0172] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this example.
[0173] Comparative Example 1 A slurry containing zirconia powder (precursor powder 1) containing 0.05 mass% alumina and 2.0 mol% yttria was prepared in the same manner as in precursor powder 1 of Example 1, except that yttria was mixed so that the yttria content was 2.0 mol%. The obtained zirconia powder had a T+C phase ratio of 5%, an average crystallite diameter of 205 Å, and a BET specific surface area of 13.6 m 2 / g.
[0174] A slurry containing zirconia powder (precursor powder 2) containing 0.05 mass% alumina and 5.5 mol% yttria was prepared in the same manner as in precursor powder 2 of Example 1, except that yttria was mixed so that the yttria content was 5.5 mol%. The obtained zirconia powder had a T+C phase ratio of 97%, an average crystallite diameter of 340 Å, and a BET specific surface area of 10.0 m 2 / g.
[0175] The difference in yttria content between the slurry of Precursor Powder 1 and the slurry of Precursor Powder 2 was 3.5 mol %. Both slurries were mixed so that the yttria content was 5.2 mol %, and then dried to obtain a zirconia powder containing 0.05 mass % alumina and having an yttria content of 5.2 mol %.
[0176] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this comparative example.
[0177] Comparative Example 2 A slurry containing zirconia powder (precursor powder 1) containing 0.05 mass% alumina and 3.0 mol% yttria was prepared in the same manner as in precursor powder 1 of Example 1, except that yttria was mixed so that the yttria content was 3.0 mol%. The obtained zirconia powder had a T+C phase ratio of 42%, an average crystallite diameter of 236 Å, and a BET specific surface area of 9.5 m 2 / g.
[0178] A slurry containing zirconia powder (precursor powder 2) containing 0.05 mass% alumina and 5.5 mol% yttria was prepared in the same manner as in precursor powder 2 of Example 1, except that yttria was mixed so that the yttria content was 5.5 mol%. The obtained zirconia powder had a T+C phase ratio of 97%, an average crystallite diameter of 340 Å, and a BET specific surface area of 10.0 m 2 / g.
[0179] The difference in yttria content between the slurry of Precursor Powder 1 and the slurry of Precursor Powder 2 was 2.5 mol %. Both slurries were mixed so that the yttria content was 5.2 mol %, and then dried to obtain a zirconia powder containing 0.05 mass % alumina and having an yttria content of 5.2 mol %.
[0180] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this comparative example.
[0181] Comparative Example 3 A slurry containing zirconia powder with an yttria content of 5.2 mol % and 0.05 mass % alumina was prepared in the same manner as in Precursor Powder 1 of Example 1, except that yttria was mixed so that the yttria content was 5.2 mol %.
[0182] The obtained slurry was dried to obtain a zirconia powder containing 0.05 mass % of alumina and 5.2 mol % of yttria.
[0183] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this comparative example. The obtained calcined body had a maximum frequency of 30%, and the difference between the maximum and minimum values of the yttria concentration was 2.2 mol%.
[0184] Comparative Example 4 A slurry containing zirconia powder with an yttria content of 5.5 mol % and 0.05 mass % alumina was prepared in the same manner as in Precursor Powder 1 of Example 1, except that yttria was mixed so that the yttria content was 5.5 mol %.
[0185] The obtained slurry was dried to obtain a zirconia powder containing 0.05 mass % of alumina and 5.5 mol % of yttria.
[0186] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this comparative example.
[0187] Comparative Example 5 A zirconia sintered body was obtained by a method according to Example 14 of Patent Document 2. That is, a slurry containing zirconia powder (precursor powder 1) containing 0.05 mass % alumina and 3.0 mol % yttria was obtained by the same method as precursor powder 1 of Example 1, except that yttria was mixed so that the yttria content was 3.0 mol %. The obtained zirconia powder had a BET specific surface area of 13.0 m 2 / g.
[0188] A slurry containing zirconia powder (precursor powder 2) containing 0.05 mass% alumina and 5.5 mol% yttria was prepared in the same manner as in precursor powder 2 of Example 1, except that yttria was mixed so that the yttria content was 5.5 mol%. The obtained zirconia powder had a T+C phase ratio of 97%, an average crystallite diameter of 340 Å, and a BET specific surface area of 10.0 m 2 / g.
[0189] The difference in yttria content between the slurry of precursor powder 1 and the slurry of precursor powder 2 was 2.5 mol %. Both slurries were mixed so that the yttria content was 4.5 mol %, and then dried to obtain a zirconia powder containing 0.05 mass % alumina and an yttria content of 4.5 mol %.
[0190] Except for using the obtained zirconia powder, molding, calcination and sintering were performed in the same manner as in Example 1 to obtain a zirconia sintered body of this comparative example.
[0191] Comparative Example 6 A molded body was obtained by a method according to Example 40 of Patent Document 3. That is, commercially available zirconia powders containing 3.0 mol % or 6.0 mol % yttria were mixed to obtain a powder made of zirconia with an yttria content of 4.2 mol %.
[0192] A zirconia sintered body of this comparative example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used and the sintering temperature was set to 1500°C.
[0193] Comparative Example 7 A molded body was obtained by a method according to Example 42 of Patent Document 3. That is, a commercially available zirconia powder containing 4.0 mol%, 5.0 mol% or 6.0 mol% yttria, an alumina powder and a magnesia powder were mixed to obtain a powder containing 0.2 mass% alumina, 0.2 mass% magnesia, and the remainder being zirconia with an yttria content of 5.5 mol%.
[0194] A zirconia sintered body of this comparative example was obtained in the same manner as in Comparative Example 6, except that the obtained powder was used.
[0195] The evaluation results of the zirconia powders of the Examples and Comparative Examples are shown in Table 1, and the evaluation results of the zirconia sintered bodies are shown in Table 2.
[0196] [Table 1]
[0197] [Table 2]
[0198] From the examples and comparative examples, it can be confirmed that even when sintered under normal pressure in an air atmosphere, the zirconia powder of the examples can obtain a zirconia sintered body having a light transmittance of more than 47%, a PT / TT ratio of 1.0 or less, and a three-point bending strength of more than 700 MPa. On the other hand, when either the T+C phase ratio or the average crystallite size is outside the range of this embodiment, it can be confirmed that the three-point bending strength is low and the transparency is high. Furthermore, from comparative examples 1 and 2, it can be confirmed that the zirconia sintered body of this embodiment cannot be obtained by simply mixing precursor powders having different yttria contents. Furthermore, from comparative example 5, it can be confirmed that when the yttria content is reduced, the translucency is insufficient and the zirconia sintered body of this embodiment cannot be obtained by simply mixing precursor powders having different yttria contents. Furthermore, in comparative examples 6 and 7, the sintered body that showed high translucency when sintered under an oxygen atmosphere in Patent Document 3 was sintered in an air atmosphere, and it can be confirmed that the light transmittance is lower than that of the examples.
[0199] Moreover, it can be confirmed that in Comparative Examples 3 and 4 obtained from a single zirconia powder, the three-point bending strength is all less than 700 MPa.
[0200] Fig. 1 shows an SEM photograph of the surface of the zirconia sintered body of Example 1. It can be confirmed that the zirconia sintered body of Example 1 contains coarse crystal grains with a major axis of 1.0 to 1.7 µm and fine crystal grains with a major axis of 0.1 to 0.4 µm. As shown by the circled parts in Fig. 1, it can be confirmed that the zirconia sintered body has a structure in which a plurality of fine crystal grains form grain boundaries with the coarse crystal grains.
[0201] Fig. 2 is a graph showing the relationship between the proportion of crystal grains with an yttria concentration of 3 to 4 mol% in the total crystal grains and the three-point bending strength for the examples and comparative examples. It can be seen from Fig. 2 that when the proportion exceeds 10%, the three-point bending strength is 700 MPa or more, and when the proportion is 25% or more, the three-point bending strength is 820 MPa or more.
[0202] In addition, the zirconia sintered body of Comparative Example 3 obtained from a single zirconia powder had a concentration difference between crystal grains of 2.65 mol%, which was less than 3 mol%, while the zirconia sintered bodies of Examples 1 to 4 having a three-point bending strength of 800 MPa or more had concentration differences between crystal grains of 3.55 mol%, 4.17 mol%, 4.77 mol%, and 3.24 mol%, all of which were 3 mol% or more. In addition, the zirconia sintered body obtained by sintering the zirconia powder obtained by the same method as in Example 1 at 1550°C had a concentration difference between crystal grains of 3.14 mol%, and it was confirmed that the concentration difference between crystal grains of the zirconia powder of Example 1 became smaller as the sintering temperature increased.
[0203] Furthermore, for the representative examples and comparative examples, the monoclinic frequency of the samples after the three-point bending strength measurement was measured. The results are shown in the table below.
[0204] [Table 3]
[0205] In all of the examples having a three-point bending strength of 800 MPa or more, the monoclinic frequency was 40% or more, and it was confirmed that the three-point bending strength tended to increase as the monoclinic frequency increased.
[0206] Example 13 The zirconia sintered body of this example was obtained in the same manner as in Example 1, except that zirconia powder obtained in the same manner as in Example 2 was used and the sintering temperature was 1550°C.
[0207] Example 14 The zirconia sintered body of this example was obtained in the same manner as in Example 13, except that zirconia powder obtained in the same manner as in Example 4 was used.
[0208] Example 15 The zirconia sintered body of this example was obtained in the same manner as in Example 13, except that zirconia powder obtained in the same manner as in Example 5 was used.
[0209] Example 16 The zirconia sintered body of this example was obtained in the same manner as in Example 13, except that zirconia powder obtained in the same manner as in Example 8 was used.
[0210] Example 17 The zirconia sintered body of this example was obtained in the same manner as in Example 13, except that zirconia powder obtained in the same manner as in Example 9 was used.
[0211] Comparative Example 8 The same procedure was carried out as in Example 13, except that a zirconia powder obtained in the same manner as in Comparative Example 1 was used. The zirconia sintered body of this comparative example was obtained by the above-mentioned methods.
[0212] Comparative Example 9 A zirconia sintered body of this comparative example was obtained in the same manner as in Example 13, except that zirconia powder obtained in the same manner as in Comparative Example 2 was used.
[0213] Comparative Example 10 A zirconia sintered body of this comparative example was obtained in the same manner as in Example 13, except that zirconia powder obtained in the same manner as in Comparative Example 3 was used.
[0214] The results are shown in the table below.
[0215] [Table 4]
[0216] Comparison of Comparative Examples 3 and 10 confirms that the average crystal grain size of the conventional zirconia powder increases with increasing sintering temperature, and the light transmittance improves accordingly. In contrast, it can be confirmed that the zirconia sintered body of the Example tends to have a lower light transmittance, even though the average crystal grain size increases with increasing sintering temperature. This confirms that the zirconia powder of the present embodiment can obtain a zirconia sintered body with higher light transmittance and mechanical strength when sintered at normal pressure at a sintering temperature of 1450°C, compared to when sintered at normal pressure at a sintering temperature of 1550°C.
Claims
1. A calcined body comprising an yttria source and zirconia, the content of the yttria source being 4.5 mol% or more and 6.5 mol% or less with the remainder being zirconia, and the maximum frequency of the distribution of yttrium concentration in a quantitative elemental analysis of an energy dispersive spectrum is less than 30%.
2. 2. The calcined body according to claim 1, wherein the difference between the maximum and minimum values of the yttria concentration in a quantitative elemental analysis of an energy dispersive spectrum exceeds 3.0 mol%.
3. The calcined body according to claim 1 or 2, which contains alumina.
4. The calcined body according to claim 3, having an alumina content of 0.005% by mass or more and 0.2% by mass or less.
5. 5. The calcined body according to claim 1, which contains at least one element selected from the group consisting of iron, cobalt, nickel, manganese, praseodymium, neodymium, europium, gadolinium, terbium, erbium and ytterbium.
6. A method for producing a sintered body, comprising pressureless sintering the calcined body according to any one of claims 1 to 5.
Citation Information
Patent Citations
Zirconia sintered body and manufacturing method therefor
JP2018052806A
Sintered body of zirconia and method for manufacturing the same
JP2011073907A
Light-transmitting zirconia sintered compact, zirconia powder and application thereof
JP2015143178A